A literature survey of financial reporting in private firms. Issue 1 (April 2018) - Habib, A.; Ranasinghe, D.; Huang, H.J.
Abstract: This paper provides a survey of the empirical literature on financial reporting in private firms. Although private firms play a dominant role in country-level economic development, research on their financial reporting is limited. The survey reveals that there remains uncertainty as to the purpose of financial reporting in private firms which is also reflected in the current body of the empirical literature. The survey provides implications for regulators with respect to regulating the financial reporting of private firms. The survey also identifies some limitations of existing research and offers potential avenues for future research.